Identification of Academic Problems in Psychology College Students at Kudus - Ratri, Prapti (Riviera Publishing, 2024)
This research focuses on identifying problems in the learning process for psychology students who are studying at universities in Central Java. This research is research using analytical descriptive methods with the research population being all students of the Psychology Study Program in Central Java and the targets of the research are students who are still actively attending lectures. The activities carried out include collecting student problems in participating in the learning process at higher education. Based on the research results, there are seven academic problems experienced by students from the Class of 2020 to the Class of 2022 from highest to lowest, including 1) Decreased motivation of 30.4%, 2) Experiencing academic stress of 18.8%, 3) Low academic integrity by 17.5%, 4) Lack of time management skills by 11.5%, 5) Academic procrastination by 9.4%, 6) Optimism decreased by 7% and 7) Academic burnout by 5.4%.